The Role of Governance Structure in Determining the Effectiveness of Fraud Prevention Strategies: A Systematic Literature Review - Mila Failasufa; Isnuhardi Isnuhardi (BUGIS : Journal of Business, Technology, & Social Science, 2026)
This study examines the role of corporate governance in determining the effectiveness of fraud prevention strategies. Using a Systematic Literature Review (SLR) approach with the PRISMA protocol, this study analyzes 21 international journal articles published between 2015 and 2026. The findings indicate that Agency Theory is the most dominant theoretical framework (48%). The majority of studies (81%) report a positive impact of corporate governance on fraud prevention, while 19% report negative effects. Governance mechanisms such as audit committees, board independence, and internal controls are found to be effective in mitigating fraud; however, their effectiveness depends on contextual factors and the quality of implementation. This study concludes that corporate governance plays a significant role in fraud prevention, but its effectiveness requires a contextual and integrated approach.